The belt-buckle with Bacchus from "Romuliana" : Pojasna kopča s Bakhom iz "Romuliane" - Guštin, Mitja (Array, 2019)
The article deals with two extraordinary gilded silver belt buckles with mythological scenes representing Bacchus, Pan, and a Maenad, reportedly found in the surroundings of Zaječar, most likely in the area of the Roman centre of ROMULIANA. The belt buckles have an excellent parallel from somewhere in “Asia Minor” with scenes of Apollo and Daphne, as well as hunting scenes, perhaps displaying Bellerophon and Chimera. Both belt buckles were associated with the highest military rank of Late Roman society, and probably produced in eastern workshops, perhaps in Constantinople. The presence of both belt buckles confirms the prominent role of this eastern part of the Roman Empire, and of Romuliana, in the period around 400 AD.